Race in modern Irish literature and culture - Brannigan, John. (Edinburgh : Edinburgh University Press, 2009)
For decades Ireland presented itself as the land of hospitality, until the 1990s, when the 'Celtic Tiger' exposed its racist underbelly. In Race in Modern Irish Literature and Culture, John Brannigan argues that race and racism have longer histories in the Irish state, histories which have often been exposed and critiqued by Irish writers and artists. He revisits the role of racial ideologies in the foundation and development of the state, offering original historical insights, and inspired new readings of literary and cultural works ranging from Ulysses to The Commitments. Key Features Provides new research on the social history of racial ideologies and racist expressions in the Irish state since 1922 Offers new readings of Irish cultural productions and literary texts (by James Joyce, W.B. Yeats, Samuel Beckett, Liam O'Flaherty, Kate O'Brien, Edna O'Brien, Brendan Behan, James Plunkett, Paul Durcan, Austin Clarke, Aidan Higgins, Denis Johnston, and others) emphasising how they engage with the histories of Irish racism and raciology Demonstrates how a new understanding of the constitutive role of race and racism in modern Irish culture might necessitate a revision of the dominant precepts and trends in contemporary Irish studies Addresses the significance of the social and cultural history of race and racism in twentieth-century Ireland for the post-'Celtic Tiger' era
Cover -- Copyright -- Contents -- Illustrations -- Acknowledgements -- Introduction -- Chapter 1 1922, Ulysses, and the Irish Race Congress -- Chapter 2 Face Value: Racial Typology and Irish Modernism -- Chapter 3 8216;Aliens in Ireland8217;: Nation-building and the Ethics of Hospitality -- Chapter 4 8216;Ireland, and Black!8217;: The Cultural Politics of Racial Figuration -- Conclusion: Imagining the 8216;New Hibernia8217; -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: English literature -- Irish authors -- History and criticism; English literature -- 20th century -- History and criticism; Race in literature; Multiculturalism in literature; Multiculturalism -- Ireland; Racism -- Ireland; Ireland -- In literature; Ireland -- Race relations; Littérature anglaise -- Auteurs irlandais -- Histoire et critique; Littérature anglaise -- 20e siècle -- Histoire et critique; Race dans la littérature.; Multiculturalisme dans la littérature.; Multiculturalisme -- Irlande; Racisme -- Irlande; Irlande -- Dans la littérature.; Irlande -- Relations raciales; 18.05 English literature; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- General; English literature; English literature -- Irish authors; Literature; Multiculturalism; Multiculturalism in literature; Race in literature; Race relations; Racism; Ireland; Kulturelle Identität; Literatur; Rasse; Irland; Racial problem; English; Literature; Ireland; Literatur; Englisch; Motiv (Literatur); Ethnische Beziehung; Kulturelle Identität; Irland; 1900-1999; 1900-2000.; Electronic books; Criticism, interpretation, etc